Straw Wine Melanoidins as Potential Multifunctional Agents: Insight into Antioxidant, Antibacterial, and Angiotensin-I-Converting Enzyme Inhibition Effects - Goulas, Vlasios; Nicolaou, Demetra; Botsaris, George; Barbouti, Alexandra (My University, 2018)
Numerous studies provide robust evidence for a protective effect of red wine against many diseases. This bioactivity has been mainly associated with phenolic fractions of wines. However, the health effects of melanoidins in red sweet wines has been ignored. The goal of the present work was to unravel the antioxidant, antimicrobial, and angiotensin-I-converting enzyme (ACE) inhibitory properties of straw sweet wine melanoidins. Results demonstrated that melanoidins have a potential antioxidant activity, determined by 2,2-Diphenyl-1-picrylhydrazyl (DPPH) and Ferric reducing antioxidant power (FRAP) assays. The antimicrobial activity of melanoidins was also tested against Listeria monocytogenes, Salmonella Enteritidis, and Escherichia coli. Minimum inhibitory concentration (MIC) of isolated melanoidins against three bacterial strains ranged from 5 mg mL-1 to 10 mg mL-1. Finally, the ACE inhibitory effect of isolated melanoidins was evaluated, as it is linked with antihypertensive activity. Results showed that they have ACE-inhibitory activity ranging from 58.2 ± 5.4% to 75.3 ± 6.4% at a concentration level of 2 mg mL-1. Furthermore, the chemical properties of isolated melanoidins were determined. Results demonstrated that the skeleton of straw wine melanoidins is mainly composed of carbohydrates, and bear significant numbers of phenolic compounds that may play critical roles in their functional properties. Overall, this study describing the chemical composition and functional properties of melanoidin fractions isolated from a straw wine highlights that they can be exploited as functional agents for multiple purposes. Finally, melanoidins are an unexplored source of bioactive molecules in straw wines except from polyphenols that contribute to the health effects.
Keywords: Commandaria wine; Escherichia coli; Listeria; Salmonella; Angiotensin I converting activity; Radical scavenging activity